Integrating Digital Technologies in ESP Classroom: A Comprehensive Overview of Current Practices and Pedagogical Implications - Dwita Laksmita Rachmawati; Nico Irawan (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
This study explores the integration of digital technologies in English for Specific Purposes (ESP) education, providing a comprehensive overview of current practices and their pedagogical implications. With the increasing reliance on technology in modern education, this study examines how digital tools, ranging from Learning Management Systems (LMS) and online collaboration platforms to specialized language learning apps are being incorporated into ESP courses. The paper discusses the benefits of using technology to tailor language instruction to the specific needs of learners in various professional and academic fields, especially in the field of economic. It also highlights challenges faced by ESP instructors, including the need for digital literacy, appropriate resource selection, and training in integrating technology effectively into curricula. Additionally, the article addresses the role of technology in fostering learner engagement, enhancing access to authentic materials, and providing individualized learning experiences. Drawing on recent research and case studies, the paper offers practical recommendations for ESP educators, suggesting strategies for overcoming barriers to technology adoption and optimizing its use in the classroom. The article concludes by considering future trends in digital technology and their potential impact on the evolution of ESP pedagogy.